Simple and rapid detection of Salmonella strains by direct PCR amplification of the hilA gene (2003)
ABSTRACT : The suitability of a PCR procedure using a pair of primers targeting the hilA gene was evaluated as a means of detecting Salmonella species. A total of 33 Salmonella strains from 27 serovars and 15 non-Salmonella strains from eight different genera were included. PCR with all the Salmonella strains produced a 784 bp DNA fragment that was absent from all the non-Salmonella strains tested. The detection limit of the PCR was 100 pg with genomic DNA and 3 3 104 c.f.u. ml 1 with serial dilutions of bacterial culture. An enrichment-PCR method was further developed to test the sensitivity of the hilA primers for the detection of Salmonella in faecal samples spiked with different concentrations of Salmonella choleraesuis subsp. choleraesuis serovar Typhimurium. The method described allowed the detection of Salmonella Typhimurium in faecal samples at a concentration of 3 3 102 c.f.u. ml 1. In conclusion, the hilA primers are specific for Salmonella species and the PCR method presented may be suitable for the detection of Salmonella in faeces.